Serological assessment of the durability of vaccine-mediated protection against SARS-CoV-2 infection - John T. Bates; Seth T. Lirette; Andrew P. Farmer; Michael A. Bierdeman; Kristina B. Seyfarth; Dallas R. Ederer; Denise D. Montgomery; Grace C. Burnett; Amanda T. Pham; Gailen D. Marshall (Human Vaccines & Immunotherapeutics)
Virus-neutralizing antibodies are often accepted as a correlate of protection against infection, though questions remain about which components of the immune response protect against SARS-CoV-2 infection. In this small observational study, we longitudinally measured spike receptor binding domain (RBD)-specific and nucleocapsid (NP)-specific serum IgG in a human cohort immunized with the Pfizer BNT162b2 vaccine. NP is not encoded in the vaccine, so an NP-specific response is serological evidence of natural infection. A greater than fourfold increase in NP-specific antibodies was used as the serological marker of infection. Using the RBD-specific IgG titers prior to seroconversion for NP, we calculated a protective threshold for RBD-specific IgG. On average, the RBD-specific IgG response wanes below the protective threshold 169 days following vaccination. Many participants without a history of a positive test result for SARS-CoV-2 infection seroconverted for NP-specific IgG. As a group, participants who seroconverted for NP-specific IgG had significantly higher levels of RBD-specific IgG following NP-seroconversion. RBD-specific IgG titers may serve as one correlate of protection against SARS-CoV-2 infection. These titers wane below the proposed protective threshold approximately six months following immunization. Based on serological evidence of infection, the frequency of breakthrough infections and consequently the level of SARS-CoV-2-specific immunity in the population may be higher than what is predicted based on the frequency of documented infections.